Results of the Test-Run of the Computer Software Model Support System for Managerial Decision Making - V. A. Safronov; A. A. Lopatin; A. S. Razdorsky; E. V. Kuklev; V. P. Toporkov; A. I. Kovtunov; N. V. Piskunova; V. V. Kabin; G. L. Shendo; O. V. Maletskaya; A. G. Bachinsky; A. V. Polovinkina (Проблемы особо опасных инфекций, 2011)
Considered is the experience of development of the decision support system (DSS) in the sphere of biological safety provision. Described are the objectives, functions, and architecture of DSS. Represented are the results of operational program-testing in the model territory (the Astrakhan region). Indicated is the effectiveness of DSS for information support of the control activity over internal and external biosafety hazards. Determined are the directions for further development of DSS.